Cloning and Characterization of a Novel Laccase Gene, fvlac7, Based on the Genomic Sequence of Flammulina velutipes - Kim, J.K., Hankyong National University, Ansung, Republic of Korea; Lim, S.H., Hankyong National University, Ansung, Republic of Korea; Kang, H.W., Hankyong National University, Ansung, Republic of Korea (Mycobiology, 2013)
Laccases are copper-containing polyphenol oxidases found in white-rot fungi. Here, we report the cloning and analysis of the nucleotide sequence of a new laccase gene, fvlac7, based on the genomic sequence of Flammulina velutipes. A primer set was designed from the putative mRNA that was aligned to the genomic DNA of F. velutipes. A cDNA fragment approximately 1.6-kb long was then amplified by reverse transcriptase-PCR using total RNA, which was subsequently cloned and sequenced. The cDNA sequence of fvlac7 was then compared to that of the genomic DNA, and 16 introns were found in the genomic DNA seqence.